2008
DOI: 10.1016/j.bbamem.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interactions of hemoglobin variants, HbA, HbE, HbF and globin subunits of HbA: Effects of aminophospholipids and cholesterol

Abstract: The interaction of hemoglobin with phospholipid bilayer vesicles (liposomes) has been analyzed in several studies to better understand membrane-protein interactions. However, not much is known on hemoglobin interactions with the aminophospholipids, predominantly localized in the inner leaflet of erythrocytes, e.g., phosphatidylserine (PS), phosphatidylethanolamine (PE) in membranes containing phosphatidylcholine (PC). Effects of cholesterol, largely abundant in erythrocytes, have also not been studied in great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The inner side of the RBC membrane is composed of phosphatidylserine lipids, but these are normally masked by membrane proteins. In cases where abnormal Hbs are increased or when membrane lipids are abnormally exposed, Hbs might interact irreversibly with the lipid layer and distort the membrane 3–6. Apart from the membrane components, Sitdikova 7 demonstrated that the Hb could also interact with serum proteins of mice with Ehrlich carcinoma.…”
Section: Routine Hematological Examination Results Of the Subjectsmentioning
confidence: 99%
“…The inner side of the RBC membrane is composed of phosphatidylserine lipids, but these are normally masked by membrane proteins. In cases where abnormal Hbs are increased or when membrane lipids are abnormally exposed, Hbs might interact irreversibly with the lipid layer and distort the membrane 3–6. Apart from the membrane components, Sitdikova 7 demonstrated that the Hb could also interact with serum proteins of mice with Ehrlich carcinoma.…”
Section: Routine Hematological Examination Results Of the Subjectsmentioning
confidence: 99%
“…The presence of membrane proteins in the samples is also supported by the recorded TEM images (Figure S1). Membrane‐bound hemoglobin molecules were observed earlier for various lipid compositions, as well as for red blood cells . It was even suggested that hemoglobin may dissociate from its tetramer form and that dimer subunits could rather associate with the membranes .…”
Section: Figurementioning
confidence: 95%
“…The buffer was prepared in triple distilled deionized water from Milli Q source (Millipore Corporation, Massachusetts, USA). 6-CF concentration was measured at 492 nm using molar absorptivity as 72 9 10 3 M À1 Ácm À1 [13].…”
Section: Methodsmentioning
confidence: 99%